The Correlation between Nurse Staffing and Nosocomial Infection Outcome in Central Thailand Hospitals - Sujijantararat, Rachanee; Chansiri, Khantarut; Sukadaecha, Rungrat; Sumdangrith, Pensri; Wipak, Cheewarat (Princess of Naradhiwas University Journal, 2023)
The objectives of this retrospective descriptive correlational research were to study the relationship between nurse staffing and Catheter associated Urinary Tract Infections (CAUTI), Ventilator associated Pneumonia (VAP), Central Line associated Bloodstream Infection (CLABSI). Sample was in-patient ward in tertiary care hospitals in Central Thailand under Department of Disease Control, Region 5. They consisted of 100 wards. The research instruments consisted of the nurse staffing record and nosocomial infection rate of each ward collected from the hospital database and related sector, calculated into yearly average rate. Data then were analyzed using Spearman rank correlation statistic. The results were disclosed as the followings. 1) The average Nursing Hour Per Patient Day (NHPPD) was 7.15 (S.D.= 5.31), the average Expected Nursing Hour Per Patient Day (Expected NHPPD) was 7.40 (S.D.= 2.37), and the average Shortage of Nursing Hour Per Patient Day (Short NHPPD) was 1.94 (S.D.= 3.60). 2) There was a significant positive correlation between Short NHPPD and CAUTI, VAP and CLABSI (r = .427, .287, .276, p < .01 consecutively). 3) Percentage of RN (Percent RN) had a positive correlation with CAUTI, VAP at p < .01 (r = .360, .384, p < .01 consecutively) and CLABSI at p < .05 (r = .249, p < .05). 4) On the other hand, Percentage of Non-Registered Nurse (Percent Non-RN) had a negative correlation with CAUTI, VAP and CLABSI at p < .01 (r = .388, .358, .325, p < .01 consecutively).